Analysis of Nene' Mallomo's Cultural Philosophy in the Management of Regional Finances and Assets in the Office of the Regional Finance and Assets Agency of Sidenreng Rappang District" - Firman; Wulan Pratiwi (IECON: International Economics and Business Conference, 2023)
The Local Government as the party given the task of running the government is obligedto report financial accountability for the resources collected from the community as a basis for assessing its financial performance. This study aims to determine the cultural philosophy value of Nene' Mallomo in the management of regional finances and assets inthe office of the Regional Finance and Assets Agency of Sidenreng Rappang Regencyand to know the value of the Nene' Mallomo cultural philosophy in expressing its role in the achievement of the Performance of the Regional Financial and Asset Agency of Sidenreng Rappang Regency. This research is a qualitative research that produces descriptive data in the form of speech/writing on the behavior of the people observed. The techniques for collecting interview data, documentation and literature studies. The results show the Financial Management of Sidenreng Rapang Regency is already very good. It can be seen from the point of view of agency theory where the government acts as an agent to give full responsibility to community by managing finances based on principles and principles and managing regional finances.